The impact of the COVID-19 lockdown on SMEs and employment relationships in Uganda - Bassi, Vittorio; Porzio, Tommaso; Sen, Ritwika; Tugume, Esau (International Growth Center (IGC) Uganda, 2021)
During 2020, governments in many developing countries introduced severe restrictions on economic activity and mobility to curb the spread of COVID-19. In Uganda, public transport and non-essential businesses were closed from early April to June 2020. These policy brief reports on the results from a phone survey of representative sample of SMEs and their workers conducted in late2020 to study how SME activity and employment relationships were impacted by a prolonged lockdown. The findings show the strict three-month lockdown resulted in significant increase in firm closures, but these closures were by and large temporary. They also uncover substantial resilience of informal labour relationships to the shock. Although most workers were let go during the lockdown and 15% of workers migrated to other locations, 76% of the furloughed employees were recalled back to work by the same employer after the lifting of the lockdown restrictions. Even though most firms reopened, and considerable shares of workers were re-hired, this has been accompanied by substantial income losses: firms are now earning 30% lower revenues and workers are earning 30% less incomes than before the lockdown. The results suggest a key role for liquidity and wage support policies to help impacted firms and workers.